Indikasi Machiavellianism Dalam Pembuatan Keputusan Etis Auditor Senior - Febryandhie Ananda; Doni Marlius (JURNAL PUNDI, 2021)
This study is a continuation of previous research which found inconsistent results. The purpose of this study is to examine the relationship between Machiavellianism and ethical decisions in earnings management in Indonesia in two forms of manipulation, namely operating manipulation and accounting manipulation. The data collection method in this study used as many as 70 respondents. Machiavellianism does not affect the ethical decisions of earnings management in a Public Accounting Firm in West Sumatra. This is because the customary system of ABS - SBK (Adat Bersandi Syara' - Syara' Bersandi Kitabullah) in West Sumatra has an impact on the Machiavellian nature of Senior Accountants, and there is a significant difference between operating manipulation and accounting manipulation.